The influence of partial deforestation on moisture regime: sums of precipitation and total soil moisture content for the territory of Ukraine based on data of numerical experiment LUMIP - Pysarenko, L.A.; Krakovska, S.V. (Geofizicheskiy Zhurnal, 2022)
The paper is dedicated to the impact of partial deforestation on sums of precipitation and part/fraction or sums of precipitation intercepted by the canopy; total soil moisture content under condition of minimal anthropogenic influence for the territory of Ukraine. In this work used data from the Land Use Model Intercomparison Project (LUMIP), which is based on Global Climate Models (GCMs). The purpose of LUMIP is to reveal patterns of changes of climate characteristics due to gradual global deforestation with a trend approximately 1 % every year and its replacement on grass or pastures for period 1850—1899. This time span is considered as the pre-industrial. The next period, 1900—1929 is without changes in forest cover. For estimation of impacts of partial deforestation the methods of anomalies over the first 20-year period (1850—1869) was used with further application of 5-year running mean of climatic characteristics to smooth their interannual variability. Coefficients of linear correlation between running mean anomalies of specific characteristic and the percentage of forest cover in grid cells with averaging over latitudinal zones, linear trends and differences were estimated. Overally estimations have shown that the global partial deforestation doesn’t impact directly on of monthly total precipitation in the middle latitudes, particularly, in Ukraine. But gradual forest reduction decreases part or fraction of precipitation intercepted by the canopy in both cold and warm seasons with average trend up to –2,6....–1,5 %/10 years in latitudinal zones in specific grids, where forest cover was reduced. The maximal decline was up to –14.5 % in grids as the difference between the 50-year period of partial deforestation and the next 30-year period. Such an effect will causemore precipitation reaching the ground and most likely will influence surface runoff. Found, that it causes the increase in total soil moisture content with trend 0.1—4.9 %/10 years depending on month and climate model, but with most significant changes during summer and autumn seasons. Thus, the analysis of LUMIP data for Ukraine has revealed that the partial deforestation caused the decrease of fraction part/fraction of precipitation intercepted by the canopy. Most GCMs demonstrated that this reduction provoked the increase of total soil moisture content and also can cause changes in hydrological regime and provoke higher flood frequency and other related hydrometeorological hazards in the forest part of Ukraine.